Board Games and Additional Language Teaching: A Proposal for Practicing Communicative Functions - Giménez García, Roser; Ibañez, Anna; Cicres, Jordi (Didáctica. Lengua y Literatura, 2025)
Games have been part of the teaching-learning process since ancient times. For some decades now, the use of games, known as Game-Based Learning (GBL), has been gaining popularity in education. In terms of second language acquisition, it offers multiple advantages, among which is its ability to increase classroom interaction, given that the most common methods are currently based on the notional-functional approach and focus on learners’ communicative competence. In this article, we use qualitative content analysis with two objectives: to classify the specific communicative functions of the Cervantes Institute’s Curricular Plan and to analyse the main components of different commercial board games. Finally, we present a proposal of fourteen games which can be used to practise the groups of functions identified in the Curricular Plan.
Keywords: game-based learning; additional language teaching; communicative competence; communicative function; content analysis